Answer:
The complete expression is
So the missing term is 16.
Explanation:
Here, the given expression is:
![x^2 + 8x +](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ekdsuhl8hygn9eneoym01uidgoon9l1tl3.png)
Let us assume the missing term =
![k^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/kn92qbnxem16z3s89cdpv26waqobkmvdp7.png)
So, the given expression becomes
![x^2 + 8x + k^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t1ju2lsvu6pba29ga8brv9gbk2u4t3oyr3.png)
Now, by ALGEBRAIC IDENTITY:
![(a +b)^2 = a^2 + b^2 + 2ab](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n6pnb3ez7wjrtj55wl0phkkpgfwkd03uui.png)
So, here applying this identity, we get
![a^2 + 2ab + b^2 = x^2 + 8x + k^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7c0esfn1q5plgpgsqo4uoy30ecv7sh2jua.png)
So on comparing, we get
![a^2 = x^2, b^2 = k^2, 2 ab = 8x = 2 (x) (4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lsa16vgrgfqc1mxad7fak9xgjbe3ym5nxu.png)
So, we get that 2 (x) (4) = 2 (a)(b)
⇒ a = x, b= 4
![\implies (a+b)^2 = (x+4)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5q23vioyvaf7obt69o00r2rdol31ldaph2.png)
So, the missing term is
![k^2 = b^2 = (4)^2 = 16](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vgvf166sbdvbhzejkqsjw5v2mt3694buma.png)
Hence, the complete expression is
![x^2 + 8x + 16](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9ujfuenipsot7kzob9ebiwjgyfuug3b390.png)